UNIVERSITY PROFESSOR’S COMPETENCES PROFILE IN ON-LINE ENVIRONMENTS: SOME KEY DESCRIPTORS - García V., Irama F.; Amaro, Rosa; Brioli, Carmen (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
The development on Distance Learning through on-line tools is becoming increasingly important at the UCV. This is shown by the interest of some professors on changing their undergraduate programs form classroom education to distance learning, most or the times not knowing the complexity that implies form the pedagogical viewpoint the development of educational experiences in on-line environments of teaching and learning. The aim of this study was to assess the competences of the professor at the UCV in order to develop high quality and certain success guarantee-based educational experiences in on-line environments of teaching and learning concerning undergraduate level at the University This assessment was carried out based on the results of the analysis regarding the current experiences in some of the schools of the UCV, compared to the theoretical model that resulted from the theoretical review of the topic, competence profile and descriptors considered as imperatives. The results will allow in the short term, the draw up of action plans faced to overcome detected weaknesses and protect the strengths, with a view to increase educational experiences from the on-line model at the UCV, without leaving aside the criterion of excellence. Furthermore, the study could provide elements to a future development of a teacher training plan in the area, pursuant to the policies of the Distance Learning System of the UCV (SEDUCV in Spanish).